2019
DOI: 10.2169/internalmedicine.2596-18
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-induced Myocarditis Successfully Treated with Corticosteroid Therapy: A Case Report and Review of the Literature

Abstract: A 62-year-old man presented to our hospital for the further evaluation and treatment of his back pain, general fatigue, and dyspnea, which had developed 4 days after the 29th administration of nivolumab to treat his lung cancer. Based on his clinical history, elevated serum cardiac enzyme values, and cardiac magnetic resonance (CMR) imaging and myocardial biopsy findings, he was diagnosed with myocarditis induced by nivolumab. Corticosteroid therapy improved his condition, and CMR performed on hospital day 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
12
0
5
Order By: Relevance
“…Immune-mediated cardiotoxicity, myocarditis, is a rare but serious side effect in NSCLC patients receiving anti-PD-1/PD-L1 immune checkpoint treatment, which needs to be recognized as soon as possible for better management (98)(99)(100). A case report showed that a 75-year-old NSCLC patient suffered a drug-induced AE of myocarditis during the ninth cycle of nivolumab treatment, and its clinical symptoms were dyspnea and acute chest pain (98).…”
Section: Myocarditismentioning
confidence: 99%
“…Immune-mediated cardiotoxicity, myocarditis, is a rare but serious side effect in NSCLC patients receiving anti-PD-1/PD-L1 immune checkpoint treatment, which needs to be recognized as soon as possible for better management (98)(99)(100). A case report showed that a 75-year-old NSCLC patient suffered a drug-induced AE of myocarditis during the ninth cycle of nivolumab treatment, and its clinical symptoms were dyspnea and acute chest pain (98).…”
Section: Myocarditismentioning
confidence: 99%
“…Väčšina publikovaných vedeckých a odborných článkov týkajúcich sa toxicity ICI donedávna neuvádzala kardiálnu toxicitu. So zvyšujúcim sa počtom pacientov, ktorí sú liečení ICI, sa postupne objavuje stále širšie spektrum ich KV nežiaducich účinkov, a to: myokarditída [10,[13][14][15][16][17][18][19][20][21], perikarditída [29,31], arytmie (predsieňové, komorové, kompletná atrioventrikulárna blokáda) [10,12,27], akútny infarkt myokardu [15], funkčné poškodenie ľavej komory [12,15,28], dilatačná kardiomyopatia [15], Tako-tsubo syndróm [30], vaskulitída [31], kardiogénny šok [8], náhla smrť [13]. Autori Escudier et al [12] publikovali v roku 2017 výsledky observačnej štúdie, ktorá analyzovala klinickú manifestáciu 30 prípadov pacientov, ktorých onkológovia odoslali pre podozrenie na kardiotoxicitu po liečbe ICI na ďalšie klinické odborné vyšetrenie.…”
Section: Kardiotoxicita Navodená Inhibítormi Imunitných Kontrolných Bunclassified
“…Pacienti boli vyšetrovaní pomocou EKG a echokardiografie a bol u nich vykonaný odber kardiálneho troponínu I a mozgového natriuretického peptidu (BNP). Medián času do manifestácie kardiotoxicity bol 65 dní od začiatku terapie, a to v rozmedzí od 2 až do 454 dní, po 1 až 33 infúziách (s mediánom 3 infúzie) [ [32] pre manažment kardiologických chorôb u pacientov liečených onkologickou liečbou je dôle-vaných iba 14 prípadov myokarditídy po nivolumabe, pričom štyria z týchto pacientov zomreli [18]. U väčšiny z doteraz opísaných prípadov sa myokarditída objavila do niekoľkých dní až týždňov po zahájení liečby nivolumabom.…”
Section: Kardiotoxicita Navodená Inhibítormi Imunitných Kontrolných Bunclassified
See 2 more Smart Citations